Bringing Up Moral Literacy in Primary School Students through the Use of Image Reflection Methods - Akhmad Afroni; Dewi Puspitasari; Agnes Widiyaningrum; Noor Malihah; Norman Nofianto; Safitri Yosita Ratri (Edukasia Islamika : Jurnal Pendidikan Islam, 2022)
Moral education is in high demand in Indonesia due to the country's increasing moral degradation. This is a qualitative study that seeks to discover scaffolding strategies used by teachers in fostering moral literacy among children through the use of image reflection media and the discovery of students' experiences revealed by children's reflections. This study included ten elementary school students from Central Java, Indonesia. Researchers used semi-structured interviews and observations to supplement research data. These were carried out in order to intermingle steps in seeking the full version participants' answers to the research questions. This study employed thematic analysis to analyze the data. The analysis was carried out in order to identify and analyze the data's repeated patterns. Despite its flaws, the research subjects were enthusiastic about using the image reflection method to promote moral literacy in early childhood. This method is expected to be used as an alternative measure in moral education, particularly at the elementary school level. Empirically, the study shows how teachers implemented the process of instilling moral values and provides examples of students' authentic voices obtained through their narratives.